(untitled) (Medico Legal Update, 2020)
Diabetic 2 mellitus is also known as non-insulin dependent diabetic mellitus. It is associated with abnormalities in carbohydrate, fat and protein metabolism and may result in the chronic complication including micro vascular, macro vascular and neuropathic disorders. The reality is that diabetes influences patients’ lives. The mere presence of diabetes deteriorates a person’s quality of life. When diabetes coexists with other chronic illnesses the effect is even worse. The objectives of the study is to assess the quality of life of type 2 diabetes mellitus patient in a selected rural area and association between the quality of life and the demographic variables. A purposive sampling technique is used to collect drug from the samples. The sample size was 93 type 2 diabetes patients at selected rural community area. The quality of life was assessed by final quolid questionnaires. The result shows that 6(6%) of sample had low level of quality of life, 79(85%) of the sample had average level of quality of life, 8(9%) of sample had high level of quality of life.